Multivariate evaluation of the family pig production system in Ca?la, Angola - Chivangulula, M.; Torres, Verena; Morais, J.; M?rio, Jefilia Nalissimo; Gabriel, R. (Cuban Journal of Agricultural Science, 2013)
For analyzing the sustainability of the family pig production system in the community 25 of the municipality Ca?la, Huambo province, Republic of Angola, in May 2011 a survey was realized to 25 pig producers within the context of a family production system, through which quantitative data was obtained. Small size breeds of slow growth but resistant to local conditions predominate under this system. A non-experimental longitudinal transversal design was applied and the multivariate statistical analysis, specifically that of main components from the correlation matrix between the indicators was used. Weight values of the variables in the components higher or equal than 0.6 were considered, according to the statistical model for impact measuring. Four main components were identified which accounted for 77.45 % of the variability of the system. The main component 1 was that accounting for higher variance, with 39.31 %. Components 2, 3 and 4 accounted for lower variance. Results demonstrate that the system is simple and of little investment. In general, families own from one to three females in extensive way. Water supply to the animals was considered adequate. The quantity of farrowings per year was approximately 1.13. It is suggested to improve the quantity and quality of the feeds; also to systematize veterinary assistance to reduce piglet mortality. It is necessary to work on pig conservation and in the development of the family production system. Key words: main components, family production system, pig